Chemokine‐mediated immune responses in the female genital tract mucosa. Issue 4 (17th March 2015) - Deruaz, Maud; Luster, Andrew D
Abstract : The genital tract mucosa is the site where sexually transmitted infections gain entry to the host. The immune response at this site is thus critical to provide innate protection against pathogens that are seen for the very first time as well as provide long‐term pathogen‐specific immunity, which would be required for an effective vaccine against sexually transmitted infection. A finely regulated immune response is therefore required to provide an effective barrier against pathogens without compromising the capacity of the genital tract to allow for successful conception and fetal development. We review recent developments in our understanding of the immune response in the female genital tract to infectious pathogens, using herpes simplex virus‐2, human immunodeficiency virus‐1 and Chlamydia trachomatis as examples, with a particular focus on the role of chemokines in orchestrating immune cell migration necessary to achieve effective innate and adaptive immune responses in the female genital tract. Abstract : The April 2015 issue contains a Special Feature on "Chemokines in cellular positioning and human disease". Chemokines serve as critical extracellular mediators of cell migration and retention. Recent studies have highlighted the importance of how cells are positioned within peripheral and lymphoid tissues for the development of timely effector and memory responses. In addition, advances in structural determination of chemokine receptor‐ligand complexes and the identification of genetic mutations that impact cell migration have brought us closer to targeting this system for the development of new anti‐inflammatory and anti‐tumor based drugs. Immunology and Cell Biology thanks the coordinator of this Special Feature ‐ Joanna Groom ‐ for her planning and input.